Correlation between hand bone mineral density and joint destruction in established rheumatoid arthritis - Mochizuki, Takeshi (J Orthop, 2017)
OBJECTIVE: We aimed to clarify the correlation between bone mineral density (BMD) and the modified total Sharp score of the hand in Japanese patients with established rheumatoid arthritis (RA). METHODS: We examined the hands of 57 patients who had RA for more than 20 years. BMD for the whole hand was measured using dual-energy x-ray absorptiometry. Concurrently, the hands were analyzed using radiography to estimate the van der Heijde-modified total Sharp score (vdH-S). RESULTS: The patients were all women with a median age of 69.7 years and RA disease duration of 29.9 years. The correlation coefficients were −0.513 (P < 0.0001) for hand BMD and vdH-S of the hand, −0.576 (P < 0.0001) for hand BMD and the erosion score of the vdH-S, and −0.339 (P < 0.0001) for hand BMD and the joint narrowing score of the vdH-S. CONCLUSIONS: Hand BMD is correlated with the vdH-S in long-established RA. The hand BMD is important for structural assessment of the hand. Additionally, we may be able to predict the vdH-S of the hand on the basis of the hand BMD in long-established RA.